STUDI KASUS : TERAPI BLOWING BALLON UNTUK MENGURANGI SESAK NAFAS PADA PASIEN ASMA - Putra Agina Widyaswara Suwaryo; Selfa Yunita; Barkah Waladani; Aprilia Safaroni (AKPER Pemkab Purworejo, 2021)
Asthma is characterized by chronic inflammation of the airways involving various mediators and interrelated inflammatory cells resulting in physiological and structural changes in the airways. Asthma treatment aims to make asthma controllable. Controllable asthma is an asymptomatic state of asthma. Breathing relaxation has many techniques including using a blowing balloon technique (inflating a balloon). The purpose of this case study is to determine the effectiveness of giving blowing balloon therapy to asthma patients with a diagnosis of ineffective breathing pattern. The method used in this research is descriptive observation method with a case study approach. The subjects in this study were 3 patients with asthma aged 13-50 years, suffering from asthma for more than 3 months, recurrence frequency 2 times/week and willing to be respondents. Therapy was carried out 5 times. The study was conducted for 2 weeks in February 2021. The results of the case study showed that the three patients gave a positive response and experienced a decrease in respiration. The average respiratory frequency of patients 21-23x/minute with complaints of reduced shortness of breath. Blowing balloon therapy to stabilize the respiratory rate of asthma patients